Longitudinal changes of snatch barbell kinematics and kinetics in an elite weightlifter - Delgado, I.; Carreker, J.; Ford, J.; LeFavi, R.; Riemann, B. (The Journal of Strength and Conditioning Research, 2021)
As the popularity in weightlifting increases, the transition from youth to adulthood in world-class weightlifters has minimally been researched. Studying the barbell kinematics and kinetics during a snatch provides insight into a lifter's efficiency through the weightlifting movement. By analyzing the lifter over their training career, we are able to document changes in the proficiency of their snatch technique. Purpose: To analyze progressive changes in snatch barbell kinematic and kinetic patterns of an elite weightlifter over a five-year period. Methods: A current youth world record holder at 62, 69, and 73 kg weight classes completed snatches using 80% of his one-repetition maximum at ages 13 (62 kg) and 19 (73 kg) years. Simultaneously, three-dimensional barbell kinematic data were recorded from a 12-camera motion analysis system from which a battery of barbell kinematic and kinetic variables were computed. Qualitative analysis of 2-dimesional barbell trajectory and kinetic quiver plots were conducted between the 2 sessions. Results: From 2014 to 2019, increases were found in: (a) total lift absolute and relative peak vertical force (126.1 and 104.5%, respectively), (b) total lift power (288.5 and 251.3%, respectively), (c) first pull absolute and relative peak vertical force (126.1 and 104.5%, respectively), (d) first pull power (265.2 and 230.2%, respectively), (e) second pull absolute and relative peak vertical force (182.7 and 155.8%, respectively), and (f) second pull power (288.5 and 251.3%, respectively). In addition, barbell trajectory showed a decrease in horizontal distance (78.6%) and peak anteroposterior displacement (85.7%) over the same time period. Likewise, peak horizontal power decreased by (97.7%) during the second pull. Conclusion: The results presented describe key performance variables that can be measured to assess and evaluate technical proficiency, strength, and power development in youth weightlifters. Training adjustments can be made to optimize these variables such that technical proficiency increases during lifters' developmental years. Future research should examine the same variables at a higher intensity and into adulthood. Practical Applications: The use of barbell kinematics and kinetics on an athletes' barbell trajectory can optimize snatch technique assessment and specificity in training programming. Any specialist that has athletes weightlifting, can use these analyses to create a base, adjust their weightlifting prescription and compare their athletes progress over their training career.